2019
DOI: 10.1002/jcla.22841
|View full text |Cite
|
Sign up to set email alerts
|

How useful is bone marrow study as an initial investigative tool without lymph node biopsy in malignant lymphoma?: Eleven years of experience at a single institution

Abstract: BackgroundBone marrow (BM) study plays an important role as initial investigation specimen of lymphoma as well as staging lymphoma. This study aimed to investigate the utility of BM studies for classification of lymphoma and evaluate features of BM involvement by lymphoma over a period of 11 years.MethodsA total of 1162 cases of BM studies for lymphoma evaluation were reviewed for the incidence of lymphoma subtypes, the percentage of marrow involvement, the pattern of involvement and discordance with histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Finally, the diagnosis of ABC DLBCL was established through a bone biopsy. A previous study revealed that different diagnoses can be made by examining lymph node biopsies and other sites of involvement, and the diagnosis concordance rate between bone marrow and lymph nodes was 84.85% ( 28 ). Most patients with discordant bone marrow involvement (BMI) progress to invasive lymphoma due to transformation of the original indolent neoplasm or benign lymphoid aggregation, and downgrading from high- to low-grade malignancy has also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the diagnosis of ABC DLBCL was established through a bone biopsy. A previous study revealed that different diagnoses can be made by examining lymph node biopsies and other sites of involvement, and the diagnosis concordance rate between bone marrow and lymph nodes was 84.85% ( 28 ). Most patients with discordant bone marrow involvement (BMI) progress to invasive lymphoma due to transformation of the original indolent neoplasm or benign lymphoid aggregation, and downgrading from high- to low-grade malignancy has also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, bone marrow status assessment cannot be completed entirely by noninvasive means of PET/CT or MRI in clinical practice. Still, it can only be achieved by invasive bone marrow examination, including blood smear, biopsy, and flow cytometry [ 7 , 8 ]. Various differentiated cells such as lymphoid, erythroid, and myeloid cells can be seen in bone marrow smears.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the BM infiltration pattern can be different [4]. BM lesions can be detected using non-invasive diagnostic methods such as MRI and PET-CT, but BM biopsy is also indicated if PET/CT is negative; in some clinical situations, BM biopsy can be the only technique providing data on the presence and degree of BM infiltration with tumor lymphoid cells [5][6][7]. Currently, aspiration cytology and trephine biopsy are believed to complement each other and increase the accuracy of NHL diagnosis [8,9].…”
Section: Introductionmentioning
confidence: 99%